A Question of Family? Youth and Gangs. (August 2014) - Young, Tara; Fitzgibbon, Wendy; Silverstone, Daniel
The role of the family as a key factor in encouraging gang membership and criminality is hotly debated. Recent political rhetoric in the UK has highlighted the correlation between 'troubled families' and the rise in youth crime and gang-related violence. This article is concerned with exploring the role of the family in the formation of gangs, gang-related criminality and desistance. The overall aim of the article is to review the research literature. It posits that the evidence that connects the family to 'gang' membership is far from conclusive and argues that the aetiology of gang formation and criminality cannot simply be reduced to poor home environments or 'broken' families.